antimicrobial susceptibility test of microorganisms isolated from sputum culture of leukaemic patients with lower respiratory tract infections - Al-Neaimy, mohammed; Al-Salloum, suhaila; Mousawy, Khalida M. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: